2022
DOI: 10.2147/idr.s348765
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Practices of Patients on Antibiotic Resistance and Use in Public Hospitals of Amhara Regional State, Northwestern Ethiopia: A Cross-Sectional Study

Abstract: Background Although inappropriate antibiotic use could contribute to the spread of antimicrobial resistance, data on the knowledge, attitude and  practice of antibiotic use and resistance among patients in north-western Ethiopia are scarce. This study assessed patients’ knowledge, attitudes and practices regarding antibiotic use and resistance in selected public hospitals of Amhara regional state, Ethiopia. Methods A cross-sectional study was conducted in selected publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 44 publications
2
15
1
Order By: Relevance
“…Similarly, participants with a college or university education, a secondary education, or a vocational education had higher knowledge scores than those with only primary education or no formal education. It corroborates the findings of Bhardwaj et al [ 17 ] in India, Sindato et al [ 18 ] in Tanzania, Geta and Kibret [ 20 ] in Ethiopia and Karuniawati et al [ 24 ] in Indonesia. There was also a statistically significant ( p < 0.05) relationship found between respondents’ knowledge and practice, knowledge and attitude, and practice and attitudes.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Similarly, participants with a college or university education, a secondary education, or a vocational education had higher knowledge scores than those with only primary education or no formal education. It corroborates the findings of Bhardwaj et al [ 17 ] in India, Sindato et al [ 18 ] in Tanzania, Geta and Kibret [ 20 ] in Ethiopia and Karuniawati et al [ 24 ] in Indonesia. There was also a statistically significant ( p < 0.05) relationship found between respondents’ knowledge and practice, knowledge and attitude, and practice and attitudes.…”
Section: Discussionsupporting
confidence: 90%
“…Inappropriate AMU and the associated risk of AMR are a growing public health issue worldwide [ 15 – 17 ]. The misuse and abuse of antimicrobials in agriculture, veterinary medicine, and human medicine have been identified as major contributors to the global spread of AMR [ 18 20 ]. The emergence and spread of antimicrobial-resistant pathogens impede the use of antibiotics for both preventative and therapeutic purposes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the reports from studies conducted in Amhara regional state, tetracycline, ampicillin, gentamicin, ciprofloxacin, and cotrimoxazole were the most frequently used groups of antibiotics in animals, 38 and ampicillin, ciprofloxacin, and tetracycline were the most frequently used groups of antibiotics. 39 Most of the isolates isolated from dairy waste and wastewater (66.7%) and beef waste and wastewater (85.7%) were resistant to ampicillin and tetracycline, respectively, and norfloxacin was the most effective antibiotic for isolates from these waste samples. This finding is inconsistent with the results reported in South Africa, which showed that ciprofloxacin and gentamicin were the most effective and erythromycin was the least effective antibiotic in the control of the bacteria in this study.…”
Section: Discussionmentioning
confidence: 95%
“…According to the reports from studies conducted in Amhara regional state, tetracycline, ampicillin, gentamicin, ciprofloxacin, and cotrimoxazole were the most frequently used groups of antibiotics in animals, 38 and ampicillin, ciprofloxacin, and tetracycline were the most frequently used groups of antibiotics. 39 …”
Section: Discussionmentioning
confidence: 99%